Levofloxacin for the treatment of pyelonephritis. (June 2013) - Rafat, Cédric; Debrix, Isabelle; Hertig, Alexandre
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Levofloxacin&logicalOpe1=OR&field2=articletitle&text2=Levofloxacin&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Levofloxacin, the l-isomer of ofloxacin has become one of the cornerstones of antibiotic therapy of pyelonephritis since its introduction in the 1990s, thanks to its exceptional pharmacokinetic (PK) and pharmacodynamic (PD) profile, broad-spectrum antibacterial action and satisfactory tolerance. However, the emergence of widespread fluoroquinolone resistance over the past decade, has prompted to re-examine its place in the treatment of urinary tract infection. Areas covered: This review covers the medical literature in any language through December 2012, on 'levofloxacin'. To identify relevant articles, the search terms 'pyelonephritis', 'urinary tract infections', 'levofloxacin', 'levaquin' and 'ofloxacin' were obtained through PubMed, MEDLINE and Clinicaltrials.gov queries. The authors focus on clinical trials, articles related to the PK and PD properties of levofloxacin as well as recent development in the mechanisms and prevalence of levofloxacin resistance. Major points stemming from international guidelines are also reviewed. Expert opinion: Levofloxacin has achieved satisfactory bacterial eradication rates and clinical success across all available trials, similar to the antibiotic comparator. High-dose (750 mg) orally administrated levofloxacin over a short 5-day course is a reasonable option for patients eligible for outpatient management. Levofloxacin is no longer a suitable option for first-line empirical treatment of pyelonephritis in areas where resistance rates are high (> 10%) when pyelonephritis is hospital-acquired. Efforts to promote fluoroquinolone-sparing agents should be encouraged and its prescription should be performed in compliance with antimicrobial guidelines.